2011
DOI: 10.3109/02699052.2011.635357
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of the trephined following bifrontal decompressive craniectomy: Implications for rehabilitation

Abstract: If the use of bifrontal decompressive craniectomies continues to increase it is important that those involved in the rehabilitation process are familiar with this rare condition. Early recognition is important so that patients can receive timely intervention and it also avoids valuable health resources being allocated to patients who cannot receive maximal benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Further, in recent years, we have witnessed a growing number of papers reporting neurological improvement of patients who underwent a cranioplasty or not whether they suffered from a previous worsening 6,8,16,18,31,34,[47][48][49][50][51] (as originally described by Grant and Norcross). 10,11,13,15,25,27,29,33,35,37,39,48 We decided to measure the improvement between 24 h and 72 h after the procedure because these patients might continue to improve despite the absence of the calvarial bone, and we observed a striking 42% objective improvement and 57% subjective improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in recent years, we have witnessed a growing number of papers reporting neurological improvement of patients who underwent a cranioplasty or not whether they suffered from a previous worsening 6,8,16,18,31,34,[47][48][49][50][51] (as originally described by Grant and Norcross). 10,11,13,15,25,27,29,33,35,37,39,48 We decided to measure the improvement between 24 h and 72 h after the procedure because these patients might continue to improve despite the absence of the calvarial bone, and we observed a striking 42% objective improvement and 57% subjective improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cranioplasty may improve the patient's psychological status, social performance, and neurocognitive functioning. 1,14,19,21 The factors that contribute to periprocedural complications, including patients' demographic information, comorbidities, surgical procedure, and under lying disease, need to be thoroughly evaluated. Previous studies that were intended to answer these questions were limited by their design or by their sample size.…”
mentioning
confidence: 99%
“…8,[17][18][19][20][21][22][23] A gradual resolution of the subimplant or endocranial dead space was previously reported in 93 percent of our primary cranioplasty patients. 6 In our experience, endocranial dead space greater than 2 cm at the time of implant placement has been associated with 9,15 Obliteration of dead space does not restore normal cerebrospinal fluid circulation and shunt function.…”
Section: Plastic and Reconstructive Surgery • November 2012mentioning
confidence: 93%